Pengembangan Media Scrapbook untuk Meningkatkan Minat Belajar Pendidikan Pancasila di SMA Negeri 1 Rantau Utara - Berliana Sinurat; Englin Sianturi; Yuli Ida Arta Simatupang (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This study aims to develop a learning medium in the form of a scrapbook as an effort to increase students’ interest in learning Pancasila Education at SMAN 1 Rantau Utara. The main problem addressed is the low level of student interest in theoretical subjects, which are often perceived as less engaging. This research employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were eleventh-grade students at SMAN 1 Rantau Utara. The feasibility test results from material and media experts indicated that the scrapbook media falls into the "highly feasible" category. The implementation of the media in the classroom showed an increase in students’ learning interest, as evidenced by their activeness, enthusiasm, and participation during lessons. Therefore, the scrapbook media can serve as an effective and innovative alternative to enhance students’ interest in learning Pancasila Education.